An assessment of the learning styles of first year medical and dental students of North Bengal Medical College, Darjeeling, West Bengal, India - Panja, Sumana; Lahiri, Pratibha Rao; Lahiri, Aditi (International Journal of Research in Medical Sciences, 2020)
Background: Learning is the act of acquiring, modifying and reinforcing existing knowledge, behavior, skills and values. This phenomenon of learning is dominated by an individual’s learning style. Learning style is a popular concept in psychology and education, and it refers to how a person learns best. This study aims to identify the Learning Styles of the first year MBBS and BDS students at NBMC by administering the questionnaire of the VARK model. Methods: This cross-sectional study was performed in the Department of Physiology at North Bengal Medical College, West Bengal after. The VARK questionnaire 7.8 version was administered to 180 first year MBBS and BDS students from the 2017-2018 batch who had volunteered for the study. The Questionnaire consisted of 16 questions, along with a scoring chart. Students were allowed to choose more than one option. If in majority of the questions they opted for a single sensory modality they were considered as unimodal learners and if they chose multiple options, they were recognized as multimodal learners. Results: The study showed 57% of the students to be multimodal learners and 43% to be unimodal learners. Read/Write was the most preferred (31.22%) sensory modality followed by kinesthetic mode (29.57%). Conclusions: As majority of our students are multimodal learners teachers should incorporate active teaching and learning strategies to cater to all types of learners. Also, as the most preferred method is Read/Write which includes googling and the use of internet to browse for information, we must try and incorporate e-learning into our curriculum.